A Case Study On Islamic Bank Malaysia Berhad: In Search For Bigger Share - Che Mamat, Che Hassan Pahmi (1999)
Islamic Bank Malaysia Bhd is the only big player in Islamic Banking in Malaysia. It is the most awaited bank by Muslims of this country. It becomes the focus of the society pertaining to the effort of Muslims community to prove the viability of1he Islamic finance system vis a vis conventional financial system. However after 14 years of its existence the bank has managed to capture only 1% of the market's share in the whole banking operation of the country. The case study covers two aspects. Part I will be the write up and Part II will be the case analysis. The case write up covers salient features of the bank pertaining to the strategic approaches to increase the market share. It includes the products and services render by the bank, financial performance and the bank's operation. Part II, the case analysis discusses major issues concerning the case. Analysis is done base on the data in Part I by using technique in strategic planning such as SOOT analysis. The recommendations is made based on the outcome of the analysis using the said tool.